The physiological regulation of glucose flux into muscle in vivo - Wasserman, D. H.; Kang, L.; Ayala, J. E.; Fueger, P. T.; Lee-Young, R. S. (The Journal of Experimental Biology, 2011)
Skeletal muscle glucose uptake increases dramatically in response to physical exercise. Moreover, skeletal muscle comprises the vast majority of insulin-sensitive tissue and is a site of dysregulation in the insulin-resistant state. The biochemical and histological composition of the muscle is well defined in a variety of species. However, the functional consequences of muscle biochemical and histological adaptations to physiological and pathophysiological conditions are not well understood. The physiological regulation of muscle glucose uptake is complex. Sites involved in the regulation of muscle glucose uptake are defined by a three-step process consisting of: (1) delivery of glucose to muscle, (2) transport of glucose into the muscle by GLUT4 and (3) phosphorylation of glucose within the muscle by a hexokinase (HK). Muscle blood flow, capillary recruitment and extracellular matrix characteristics determine glucose movement from the blood to the interstitium. Plasma membrane GLUT4 content determines glucose transport into the cell. Muscle HK activity, cellular HK compartmentalization and the concentration of the HK inhibitor glucose 6-phosphate determine the capacity to phosphorylate glucose. Phosphorylation of glucose is irreversible in muscle; therefore, with this reaction, glucose is trapped and the uptake process is complete. Emphasis has been placed on the role of the glucose transport step for glucose influx into muscle with the past assertion that membrane transport is rate limiting. More recent research definitively shows that the distributed control paradigm more accurately defines the regulation of muscle glucose uptake as each of the three steps that define this process are important sites of flux control.